Capstone-P :: Rapid Search / Siti Asilah Ahmad ... [et al.] - Ahmad, Siti Asilah; Abd Latif, Nur Izzati; Yahaya, Nor Affidah; Azmi, Nur Asyirah; Mohamad Shamsul Kahar, Nur Syazwani (Universiti Teknologi MARA, Kedah, 2023)
The purpose of this project is to assist Kolej Poly-Tech Mara (KPTM) Bangi's Year 3 Bachelor of Arts (Honours) in Accounting and Finance (BAAF) students in completing a capstone project because they are struggling to get started. Therefore, Capstone-P :: Rapid Search is becoming a platform which would be helpful for students and supervisors to do a capstone project. This platform provides the title, abstract, keywords, variables and information related to the publication of previous capstone projects. This project aims to describe the development of Capstone-P :: Rapid Search using the Google Data Studio and Google Sites as the platform. ADDIE Model was used as the methodology which is an instructional design method that can help researcher plan and run smoothly the creation of their course content. In ADDIE Model, there are five stages of a development process that stands for analysis, design, development, implementation, and evaluation. The purpose of our study is to establish validity for the research results using a small number of users. Primary data was used in this project, where the data were collected through questionnaires from Year 3 BAAF students at KPTM Bangi. The questionnaire consists of two sectors which are Section A for Demographic Profile and Section B for Usage of Website. The responses are unanimous in their agreement that the Capstone-P :: Rapid Search website is effective and suited for the usability and learning process, as indicated by the questions' ranking of 4. The majority of users genuinely think the Capstone-P :: Rapid Search website is beneficial, as indicated by the median and mode of this construct, which are both 4. The average respondent agrees that the Capstone-P: Rapid Search website has the capabilities expected, is easy to navigate, is flexible to access, is effective, and is suited.